(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article talks about Cholpon’s ways to get rid of "bad luck" in literature, his enthusiasm in the process of social renewal. In addition, in this article you can see the analysis of several literary and critical heritages of Cholpon.